1982
DOI: 10.1002/kin.550140302
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and energetics of the criegee intermediate in the gas phase. I. The criegee intermediate in ozone–alkene reactions

Abstract: The chemistry and energetics of the Criegee intermediate, a primary product of the ozonolysis of alkenes, are discussed in terms of recent ab-initio calculations and laboratory studies. The experimental observations in 03-alkene systems can be rationalized on the basis of a general mechanism:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…However, experimental evidence points to direct production of O(3P) from the Criegee biradical, which then reacts with isoprene to form the epoxides, as proposed by Herron et al [19];…”
Section: -Ethenyl G-methyl Oxiranementioning
confidence: 93%
See 1 more Smart Citation
“…However, experimental evidence points to direct production of O(3P) from the Criegee biradical, which then reacts with isoprene to form the epoxides, as proposed by Herron et al [19];…”
Section: -Ethenyl G-methyl Oxiranementioning
confidence: 93%
“…Despite extensive mechanistic work on the breakup of the ozonide [2,3,6,7,[11][12][13][14]18,19] a mechanism has yet to be developed that can satisfactorily explain the large quantities of OH that clearly form in the 03-alkene systems, the formation of carbonyls (methacrolein and methyl vinyl ketone), propene, and epoxides (2-ethenyl 2-methyl oxirane and 2-( 1-methylethenyl) oxirane). In an effort to construct a mechanism that accounts for all of the available data, we propose the following mechanism for the ozone oxidation of isoprene: This mechanism assumes that the initial O3 attack occurs primarily at the unsubstituted double bond.…”
Section: Oxone-isoprene Oxidation Mechanismmentioning
confidence: 99%
“…This acid is formed in a high energy state and may undergo dissociation if not quenched (Bunnelle, 1991;Herron et al, 1982). Numerous calculations summarized by Bunnelle (Bunnelle, 1991) indicate there is a considerable activation energy barrier between a thermally equilibrated CI and the dioxirane.…”
Section: Overview Of Ozonolysismentioning
confidence: 99%
“…The reaction of ozone with alkenes, such as ethene, is initiated by cycloaddition of ozone across the double bond in ethene, forming a primary ozonide (POZ), according to Criegee [2] . POZ : CH 2 OO ≠ + M→CH 2 OO +M (R2e) The lifetime of CH 2 O 2 radicals is sufficiently long to react with numerous atmospheric species [4] , among which H 2 O has received much attention due to its ubiquitous existence on the earth and abundance in the atmosphere. The reaction of CH 2 O 2 with H 2 O was studied initially by Hatakeyama et al [5] who observed HC 18 OOH and HCO 18 OH but HC 18 O 18 OH in the product of CH 2 O 2 + H 2 18 O reaction, and therefore suggested that the reaction may have a pathway resulting in an intermediate of HMHP.…”
mentioning
confidence: 99%
“…Suto [9] obtained k 3 of 1.6×10 −17 -1.6×10 −15 cm 3 ·molecule −1 ·s −1 based on the dependence between H 2 SO 4 aerosol formation rate and concentration of O 3 , SO 2 and H 2 O in C 2 H 4 /O 3 /SO 2 /H 2 O system. Herron [4] estimated k 3 ranging from 2×10 −19 -1×10 −15 cm 3 ·molecule −1 ·s −1 using a relative rate technique. Obviously, the reported k 3 are of high uncertainty.…”
mentioning
confidence: 99%